Investigating interventions that lead to the highest treatment retention for emerging adults with substance use disorder: A systematic review. (November 2021) - Dalton, Kathryn; Bishop, Lisa; Darcy, Stephen
Highlights: Emerging adults (ages 18-25) have the highest rate of substance use disorder. Emerging adults drop out of treatment earlier than those age 26+. Retention in treatment leads to sobriety and/or harm reduction and overall improved quality of life. Highest treatment retention for alcohol/cannabis use disorder includes CBT and CM. Highest treatment retention for opioid use disorder includes CBT paired with ORT. Abstract: Background and Aims: Emerging adults (age 18–25) have the highest rate of substance use disorders (SUD) and often drop out of treatment earlier than those age twenty six or older. In order to increase treatment retention in emerging adults, there needs to be a better understanding of which SUD treatment interventions work best for this population. The purpose of this systematic review was to evaluate treatment interventions for emerging adults with SUD and identify which interventions show promise for retention in treatment. Methods: Following the PRISMA guidelines, Medline, PsycInfo, CINAHL (all via EBSCO), and Embase were systematically searched for articles that evaluated treatment interventions for emerging adults with SUD. From here, the authors identified treatment interventions that showed promise for retention in treatment. Results: Nine studies were included. The main findings indicate (1) behavioral therapy such as cognitive behavioral therapy and contingency management for cannabis and alcohol use disorders, or (2) cognitive behavioral therapy paired with opioid-agonist-therapy for opioid use disorder demonstrate the most promise for retention in treatment. Conclusion: The interventions identified that show promise for emerging adults was similar to studies evaluating interventions for all ages. Given that retention rates are often lower in emerging adults despite the application of the full range of effective adult treatments, this review suggests they may require something different. While further studies are warranted to determine with more certainty what works best to keep emerging adults in treatment, some tentative suggestions are included.